Avaliação do papel da velocidade de processamento e da memória verbal de curto-prazo no desenvolvimento da linguagem de crianças prematuras - Camila Soares de Abreu (2015)
The present study examined language ability in preterm children as well as the influence of processing speed and verbal short-term memory on the development of that ability. Participants were 45 preterm children (21 boys) from low socioeconomic (SES) families, ranging in age from 4 to 5 years (M = 54,82 months SD = 2,09). A group of 45 children born at term, matched with the premature children for age, nonverbal intelligence and SES participated as controls. Participants were administered tests that assess expressive language, vocabulary, nonverbal intelligence, processing speed (verbal and non-verbal), and verbal short-term memory (digit span and phonological memory). There were no significant differences between the two groups on either expressive language or vocabulary. However, several of our findings suggest that preterm children are more vulnerable to experience difficulties in language development than children born at term. For example, there was a tendency for the group of preterm children to perform significantly lower than the control group on the vocabulary test. The preterm children also showed more variation than controls on both language tests. Last but not least, they performed significantly lower than the full-term children on tests that assess abilities strongly associated with language development of language, namely, processing speed and verbal short-term memory. Indeed, the results of correlation and regression analysis showed that variations in processing speed and verbal shortterm memory contributed significantly to variations in language ability, both among the preterm children and the full-term children.